Medication Adherence of Latino Children and Caregivers: An Integrative Review. (December 2020) - Foronda, Cynthia L.; Muheriwa, Sadandaula Rose; Fernandez-Burgos, Margo; Prather, Susan; Nersesian, Paula
Introduction: There are significant disparities in medication adherence among underserved minority groups such as Latinos. Adherence to medication is a primary determinant of treatment success. Little is known about medication adherence among Latino children. This integrated review aims to describe what is known about medication adherence among Latino children and explore barriers and facilitators to medication adherence. Method: This review was guided by Whittemore and Knafl's method of integrative review and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Statement. Results: Of the 20 articles reviewed about medication adherence among Latino children, the analysis of these articles revealed four major themes: (1) low adherence, (2) low adherence associations, (3) child outcomes, and (4) effective interventions. Conclusion: Health practitioners should consider medication adherence associations and interventions when collaborating with the family caregiver to improve child outcomes.